ANALYTICAL STUDY AND PERFORMANCE EVALUATION OF A LAB-SCALE GREYWATER TREATMENT PLANT - I.I. Nwajuaku; O.E Ekenta; N.E Nwaiwu (European Scientific Journal, ESJ, 2015)
This study presents the recycling of greywater for non-potable applications such as toilet flushing, concrete production, and irrigation. In this study, a laboratory-scale greywater treatment plant was designed and fabricated to treat greywater with a combination of physical and natural treatments systems. These natural systems include natural-draft aerator system, coagulation by natural coagulant (Moringa Oleifera), and filtration by sand and sawdust filter media. A total of five samples of raw greywater were collected every morning from two female hostels, namely Prof. Dora Akunyili and Chief Stella Okoli hostels in Nnamdi Azikiwe University, (NAU) Awka,Nigeria. These samples were analyzed for turbidity, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solid (TSS), total dissolved solid (TDS) and total hardness. Analysis of Variance (ANOVA), Coefficient of variance and Correlation Matrix were used to analyse data obtained. Differences in parameter concentration between the influent and effluent parameters were considered significant at 5% level of significance (i.e p ≤ 0.05). The concentration of these parameters decreased significantly as a result of the treatment. Coefficient of Variation indicates that most influent and effluent parameters have coefficient of variations that are less than 10% meaning that the raw greywater samples were well collected and consistent in quality. A correlation matrix show that biochemical oxygen demand (BOD), turbidity and total suspended solid (TSS) are strongly related. This shows that the system is consistent in treatment and may be adopted for treatment of greywater for non-potable uses in areas with limited water supply.